Mining terms in the history of English: a lexical analysis of vocabulary related to boring, drilling and extraction, to ventilation, pipelines and hauling - Landmann, Julia; Landmann, Andreas (English today, 2023)
Mining is a broad and complex field. The search for and exploitation of minerals is unceasing in many countries worldwide. Before its collapse towards the close of the 20th century, coal mining in the United Kingdom, for instance, which dates back to Roman antiquity, occurred in various regions of the country, such as Northumberland and Durham, North and South Wales, Yorkshire, Kent, and the East and West Midlands. An essential aim of the present paper is to give an overview of the plethora of mining terms in English which have been coined due to progress and advance in this field over time, ranging from terms associated with boring, drilling and extraction, to ventilation, pipelines and hauling. The Oxford English Dictionary Online (Murray et al., 1884-; henceforth referred to as the OED) and specific sources such as Elsevier's Dictionary of Mining and Mineralogy (Dorian, 1993) constitute valuable tools to identify these types of lexical items. This study relies on the analysis of a comprehensive lexicographical sample of 217 mining terms documented in English.
"Published online by Cambridge University Press: 07 December 2022".- Frontdoor des Artikels
Gesehen am 08.07.2024